'Nous avons une reconstitution à reconstituer': Re-enacting the Mystery of the Yellow Room. (2nd October 2017) - Rees, Kate
Abstract : This article considers the most recent film adaptation of Gaston Leroux's Le mystère de la chambre jaune, the 2003 version directed by Bruno Podalydès, as a production which 'palimpsestuously' brings out the self-reflexive qualities of the original text. Leroux's detective novel can be seen, intertextually, as a series of embedded narratives, symbolized by the enclosed walls of the locked Yellow Room itself. Focus falls in particular on the representation of newspapers in the novel, an echo of practices at work in Poe's early detective stories, which cut and paste newspaper reports as fictionalized source texts. As in Poe's tales, such texts are challenged and pastiched by the broader narrative of the novel. Podalydès' film incorporates its own embedded narratives via the inclusion of newspapers, photography and theatre, and accentuates the ludic quality of Leroux's text through the frequent images of toys and gadgets which give visual significance to cogs and levers, making manifest the workings of the contraptions as Leroux exposes the workings of narrative in his mystery novel. This article will examine Podalydès' embracing of the self-awareness of its source text and the way it playfully points to multiple points of origin.